Complete labial fusion with urinary incontinence in a postmenopausal woman: A case report - Rakan Kotoku; Yuji Orita (Elsevier, 2022)
An 83-year-old woman presented to a rural general hospital with urinary incontinence. She was diagnosed with complete labial fusion caused by genitourinary syndrome of menopause. She was successfully treated with surgical separation followed by hydrocolloid dressings. Genitourinary syndrome of menopause often remains undiagnosed due to patient embarrassment. Greater recognition of this condition in primary care can improve patient access to appropriate treatment and improve quality of life.